2007
DOI: 10.1111/j.1360-0443.2007.01885.x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is associated with first‐ever incidence of mental disorders: a prospective population‐based study

Abstract: Aims It is well established that tobacco use is associated with mental disorders. However, the association between tobacco use and mental disorders has not yet been examined sufficiently in prospective, population-based studies. The current study is aimed at examining whether smoking is associated with first-ever incidence of mental disorders. Design, setting and participants We conducted a prospective, population-based epidemiological study (the Netherlands Mental Health Survey and Incidence Study: NEMESIS) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(71 citation statements)
references
References 31 publications
4
65
2
Order By: Relevance
“…However, other studies have concluded the opposite: substance abuse is associated with worse mental health, following epidemiological or clinical diagnostic criteria (Cuijpers, Smit, Have, & de Graaf, 2007;Farrell et al, 2003;Martínez-Ortega, Jurado, Martínez-González, & Gurpegui, 2006;Regier et al, 1990). However, an important difference between those studies and the present one is that the mental health was self-rated by the prisoners in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…However, other studies have concluded the opposite: substance abuse is associated with worse mental health, following epidemiological or clinical diagnostic criteria (Cuijpers, Smit, Have, & de Graaf, 2007;Farrell et al, 2003;Martínez-Ortega, Jurado, Martínez-González, & Gurpegui, 2006;Regier et al, 1990). However, an important difference between those studies and the present one is that the mental health was self-rated by the prisoners in the current study.…”
Section: Discussioncontrasting
confidence: 74%
“…Several studies report that individuals with high anxiety are more likely to smoke [58,61,62,63]. Many factors were accused in this association such as the use of cigarettes as a self-treatment to reduce anxiety and the increased effect of peer pressure in those suffering from anxiety [64,65].…”
Section: Discussionmentioning
confidence: 99%
“…Many factors were accused in this association such as the use of cigarettes as a self-treatment to reduce anxiety and the increased effect of peer pressure in those suffering from anxiety [64,65]. Moreover, many studies suggest that smoking increases the risk of developing high anxiety [62,66,67], 66,67] this link may be due to the effects of smoking on neurotransmitters, neurobiology, respiratory health and autonomic control [68] and due to the impact on normal neurodevelopment [69]. Finally, many shared risk factors have been identified that can increase the probability of both smoking and anxiety such as low socio economic status [70,71,73].…”
Section: Discussionmentioning
confidence: 99%
“…However, smoking is associated not only with the prevalence but also with first-ever incidence of mental disorders (Cuijpers et al, 2007). In a prospective, population-based epidemiological study, people who smoked but had no history of mental disorder had an increased risk of developing such a disorder; this risk remained significant after correcting for major risk indicators of mental disorders (incidence rate ratio RR = 1.56, P<0.05).…”
Section: Increased Levels Of Smokingmentioning
confidence: 99%